Increasing the stability of underground mining using the method of advanced fastening of soil-concrete - O. A. Volkova; Yu. A. Arsentyev; S. V. Ilaykhin; A. P. Nazarov (Известия высших учебных заведений: Геология и разведка)
One of the most effective methods in the geotechnical construction at the urban conditions, which allows providing the stabilization of the rocks and elimination of the ingress of water into the mine workings, in a short time and with minimal damage, is the jet technology (JetGrouting) of fixing of the soils. But with all advantages of JetGrouting technology, its wide application is constrained by the lack of the methodology for choosing the ratio of the fixed space volume to the unfixed, which significantly complicates the appointment of design characteristics of the system «mine working-massif of rocks to be fixed». In this regard, it was necessary to carry out the mathematical modeling of the parameters of this system. Engineering-geological conditions typical for the central part of Moscow have been accepted as initial data. The substantiation of design parameters of the system during the penetration of mining with round section in weak soils by their advanced fixing by a grouting has been presented.